A novel conformational B-cell epitope prediction method based on mimotope and patch analysis. (7th April 2016) - Sun, Pingping; Qi, Jialiang; Zhao, Yizhu; Huang, Yanxin; Yang, Guifu; Ma, Zhiqiang; Li, Yuxin
Abstract: A B-cell epitope is a group of residues on the surface of an antigen that stimulates humoral immune responses. Identifying B-cell epitopes is important for effective vaccine design. Predicting epitopes by experimental methods is expensive in terms of time, cost and effort; therefore, computational methods that have a low cost and high speed are widely used to predict B-cell epitopes. Recently, epitope prediction based on random peptide library screening has been viewed as a promising method. Some novel software and web-based servers have been proposed that have succeeded in some test cases. Herein, we propose a novel epitope prediction method based on amino acid pairs and patch analysis. The method first divides antigen surfaces into overlapping patches based on both radius ( R ) and number ( N ), then predict epitopes based on Amino Acid Pairs (AAPs) from mimotopes and the surface patch. The proposed method yields a mean sensitivity of 0.53, specificity of 0.77, ACC of 0.75 and F -measure of 0.45 for 39 test cases. Compared with mimotope-based methods, patch-based methods and two other prediction methods, the sensitivity of the new method offers a certain improvement. Our findings demonstrate that this proposed method was successful for patch and AAPs analysis and allowed for conformational B-cell epitope prediction. Highlights: A novel epitope prediction method based on amino acid pairs and patch analysis. Predict epitopes based on AAPs from mimotopes and the surface patch. Gives out the sensitivity of 0.53, the specificity of 0.77, the ACC of 0.75 Comparing with other methods, the sensitivity of the new method all has improvement.